Traditional/folk practices of Kerala Case Studies - Part 3 : Kalaripayattu - S. Rajasekharan; T. G. Vinodkumar; M. Navas; P. G. Latha (Journal of Traditional and Folk Practices (JTFP), 2016)
The practice of Kalaripayattu is a very popular traditional martial art of Kerala. This is an art and cultural expression practised in the southern most part of India, especially in Kerala for conditioning the spiritual, mental and physical faculties of an individual to lead a healthy long life. It is still practised through guru-sishya parampara. The rituals and physical practices of Kalaripayattu literally enthrals the audience and is popular in India and abroad. It is practiced by an individual or group, to defend or fight against the opponents. Kalari is also used as a self-defensive mechanism. In this communication, the authors highlight three case studies, which include studies on food and medicine exclusively consumed by the practitioners during the Kalari practice in Kerala.